NF-κB inhibition attenuates sympathetic hyperreflexia and concomitant development of autonomic dysreflexia and immune dysfunction after spinal cord injury - Micaela L. O’Reilly; Mariah J. Wulf; Theresa M. Connors; Ying Jin; Frank Bearoff; Nan Hai; Julien Bouyer; Sandhya Kortagere; Yinghui Zhong; John R. Bethea; Veronica J. Tom (Communications Biology)
Abstract Heightened sympathetic reflexes (sympathetic hyperreflexia, SH) post-high-level spinal cord injury (SCI) detrimentally impact effector organs, resulting in peripheral immune dysfunction and cardiovascular disease, two leading causes of morbidity and mortality in SCI. We previously found that an activated neuroimmune system after SCI contributes to intraspinal plasticity in the spinal sympathetic reflex (SSR) circuit, underlying SH. We hypothesize that activation of NF-κB, a key regulator of inflammation, in spinal cord below-SCI contributes to driving SSR circuit plasticity, resulting in SH-associated autonomic dysreflexia (AD) and peripheral immune dysfunction. Here, we demonstrate inhibition of central NF-κB signaling via intrathecal delivery of dimethylamino parthenolide (DMAPT) significantly decreases SH post-complete transection of thoracic spinal segment 3 in adult rats. This included reduced AD severity that was associated with decreased interneuron recruitment into the SSR circuit after SCI. We also observed intrathecal DMAPT-treatment improved survival post-SCI that corresponded with normalized numbers of splenic regulatory T-cells. These findings underscore central NF-κB signaling as a key component driving SH after SCI.